2018
DOI: 10.3390/met8121008
|View full text |Cite
|
Sign up to set email alerts
|

The Macroscopic Flow direction and Microscopic Distribution of Mg in Sintered Products and Its Influence

Abstract: Magnesium flux is an indispensable part of sintering materials. Its distribution and reaction behavior have an important influence on the quality of the sinter. Studying the macroscopic flow direction and microscopic distribution of MgO in sintered products is important for guiding the matching of ore for sintering and adjusting sintering technical parameters. The macroscopic flow direction situation of MgO in all sintered products was studied using X-Ray diffractometer and X-Ray fluorescence analyzer. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Moreover, high-basicity sintered ores are dominated by the calcium ferrite phase, which leads to elevating the yield and quality of the ore. Xin et al [9] found that an increase in basicity and Al 2 O 3 is detrimental to the formation of glassy phases in sintered ores. Wu et al [10] investigated the effect of Mg 2+ on the properties of single minerals in sintered ores. The results showed that the solid solution of Mg 2+ in single minerals was in the order of magnetite, silico-ferrite of calcium and aluminum (SFCA), silicate, and hematite, and the solid solution of Mg 2+ prevented the oxidation of magnetite to hematite, the coarsening of the grains of SFCA, and an increase in the content of silicate.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high-basicity sintered ores are dominated by the calcium ferrite phase, which leads to elevating the yield and quality of the ore. Xin et al [9] found that an increase in basicity and Al 2 O 3 is detrimental to the formation of glassy phases in sintered ores. Wu et al [10] investigated the effect of Mg 2+ on the properties of single minerals in sintered ores. The results showed that the solid solution of Mg 2+ in single minerals was in the order of magnetite, silico-ferrite of calcium and aluminum (SFCA), silicate, and hematite, and the solid solution of Mg 2+ prevented the oxidation of magnetite to hematite, the coarsening of the grains of SFCA, and an increase in the content of silicate.…”
Section: Introductionmentioning
confidence: 99%